Investigating the effect of positive psychology on improving hope, happiness and psychological flexibility of female elementary school teachers in Rafsanjan city - faezeh balochi.marj; parisa zare; Hakimeh Soleimani (مجله علوم روانشناختی)
Background: Positive psychology is the scientific study of optimal and desirable human functions. Psychologists following this trend claim that their techniques not only reduce the level of depression in individuals and societies, but also teach people the right way to live and, as a result, satisfaction with life and ultimately happiness. According to the researcher's studies, it was found that less research has been done in the field of the effect of positive psychology on improving hope, happiness and psychological flexibility of female teachers and most of the research has been done in the field of the effect of positive psychology on the happiness and hope of the elderly, the happiness of people with depression, the effect of positive psychology on life and happiness, flexibility, stress reduction, and the effect of positive thinking on strengthening and improving relationships with oneself and others. Aims: The present study aimed to investigate the effect of positive psychology on improving the hope, happiness, and psychological flexibility of female primary school teachers in Rafsanjan city. Methods: The current research method is a quasi-experimental type of pre-test and post-test. The statistical population of this research includes female primary school teachers in Rafsanjan city in the academic year 2021-2022, whose number is 510. Among these teachers, 40 people were selected through available sampling in two groups of 20 people, test and control. The measurement tools of the research were the positive psychology training package (Seligman et al., 2005), questionnaires of hope (Snyder, 2000), happiness (Hills and Argyle, 2002), and psychological flexibility (Dennis and VanderWaal, 2010). The therapy sessions consisted of 8 sessions, one session per week and each session was 90 minutes, which was held virtually using Skype software, and the teachers who had obtained the lowest score from the questionnaires of happiness, hope, and psychological flexibility, were under positive psychology group training. were placed The pre-test and post-test were taken from the teachers of both groups during two separate sessions before the beginning of the sessions (pre-test) and after the end (post-test). Results: The results show that positive psychology training improves teachers' hope with an effect size (0.86), improves teachers' happiness with an effect size (0.89), and improves teachers' psychological flexibility with an effect size (0.97). Conclusion: The results showed that positive psychology training affects improving hope, improving happiness, and improving psychological flexibility of teachers. Positive psychotherapy helps teachers to adapt all the negative events that happen in life with positive events and achieve balance in their lives.